Advising the Central America Agricultural Council on Greenhouse Gas Inventories and the contribution of the agricultural sector to climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
A series of training/advising sessions was offered to decision-makers from ministries of agriculture and environment from Central American countries on climate change, GHG accounting and mitigation practices.